Brain-derived neurotrophic factor plasma levels in patients with Turner syndrome. (March 2014) - Czyzyk, Adam; Casarosa, Elena; Luisi, Michele; Podfigurna-Stopa, Agnieszka; Meczekalski, Blazej; Genazzani, Andrea Riccardo
Abstract Introduction: Brain-derived neurotrophic factor (BDNF) plays a key role in neural development and synaptic plasticity. BDNF is known to circulate in plasma and its levels are strictly linked to the sex hormones. Aim: The aim of this study was to assess the plasma BDNF concentration in patients with Turner syndrome (TS). This is a first of such study in TS women. Methods: 31 TS patients were enrolled to the study and compared with a control group (10 healthy, ovulatory women). We collected blood for measurement of BDNF plasma concentration, estradiol (E2) and gonadotrophins serum levels. The blood was taken after overnight fasting, in menstruating women in follicular phase. Results: We found that BDNF plasma concentration was significantly higher in the group of TS patients compared to the control group (mean 768.5 ± 194.9 pg/ml versus 407.2 ± 25.7 pg/ml; p < 0.0001). What is more, the BDNF levels in TS were not correlated to E2 levels, whereas in the control group, positive and strong correlation with E2 was found (r = 0.92; p < 0.0001). The testosterone concentration correlated strongly with BDNF levels in TS patients. Conclusions: In this study, we showed for the first time that TS patients has a higher BDNF levels than healthy ones and BDNF is not correlated with E2 concentration but tend to be related to testosterone. This study brings interesting insights to BDNF physiology.